PELATIHAN PENINGKATAN KOMPETENSI GURU GEOGRAFI KABUPATEN INDRAMAYU PADA MATERI PEMETAAN DENGAN DRONE DAN TEKNIK ANALISIS VEGETASI MANGROVE - Sodikin Sodikin; Mirza Permana; Rahmat Hidayat; Agnes Puspitasari Sudarmo; Asep Andri Astriyandi (UNIVERSITAS PGRI MADIUN, 2026)
Abstract. The development of geospatial technology requires geography teachers to be able to integrate modern mapping technology into the learning process. However, the use of drones and mangrove vegetation analysis techniques is still relatively limited among geography teachers. This community service activity aims to improve the competence of geography teachers in Indramayu Regency in the use of drones for mapping and mangrove vegetation analysis techniques. The activity was carried out over two days using lectures, demonstrations, field practice, and mentoring methods. Participants in the activity consisted of 18 teachers who are members of the Indramayu Regency Geography MGMP. The activity was evaluated using a Google Form-based questionnaire completed by participants after the activity was completed. The evaluation results showed a very high level of participant satisfaction with an average score of 4.95 out of 5, or a satisfaction index of 99%. Indicators with the highest scores included material quality, resource person competence, field practice, and increased understanding of the mangrove ecosystem. This activity successfully improved teachers' perceived understanding and skills, based on the participants' selfassessments. Abstrak. Perkembangan teknologi geospasial menuntut guru geografi untuk mampu mengintegrasikan teknologi pemetaan modern ke dalam proses pembelajaran. Namun demikian, pemanfaatan drone dan teknik analisis vegetasi mangrove masih relatif terbatas di kalangan guru geografi. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kompetensi guru geografi Kabupaten Indramayu dalam pemanfaatan drone untuk pemetaan dan teknik analisis vegetasi mangrove. Kegiatan dilaksanakan selama dua hari dengan metode ceramah, demonstrasi, praktik lapangan, dan pendampingan. Peserta kegiatan terdiri atas 18 guru yang tergabung dalam MGMP Geografi Kabupaten Indramayu. Evaluasi kegiatan dilakukan menggunakan kuesioner berbasis Google Form yang diisi oleh peserta setelah kegiatan selesai dilaksanakan. Hasil evaluasi menunjukkan tingkat kepuasan peserta yang sangat tinggi dengan nilai rata-rata 4,95 dari skala 5 atau indeks kepuasan sebesar 99%. Indikator dengan nilai tertinggi meliputi kualitas materi, kompetensi narasumber, praktik lapangan, serta peningkatan pemahaman mengenai ekosistem mangrove. Kegiatan ini berhasilmeningkatkan persepsi pemahaman dan keterampilan guru berdasarkan penilaian mandiri peserta.